Congenital Splay Leg Syndrome in Piglets—Current Knowledge and a New Approach to Etiology - Schumacher, Toni; Röntgen, Monika; Maak, Steffen (Frontiers in Veterinary Science, 2021)
The porcine congenital splay leg syndrome (PCS), even though being of transient nature, is still one the most important causes for piglet losses due to its high incidence and mortality. Although, described decades ago, the pathogenetic mechanism is still elusive. Numerous, mostly descriptive studies characterized the syndrome at clinical, histological and cellular level but resulted in a highly diverse picture of the syndrome. Broad variability in phenotypical expression and, in case of proper care, the rapid recovery of affected animals complicated a systematical analysis of the underlying pathogenesis. Although, it is long established that PCS is hereditary, only few of the suggested candidate genes from transcriptome and mapping analyses, like F-box protein 32 (FBXO32), could be confirmed so far. Only recently, a genome wide association study revealed genomic regions on five porcine chromosomes and named a number of potential candidate genes, among them homer scaffold protein 1 (HOMER1). This new candidate - a cellular scaffold protein – plays a role in a plethora of cellular signaling cascades, and is not only involved in skeletal muscle differentiation but also critical for muscular function. In this review, we critically elucidate the current state of knowledge in the field and evaluate current achievements in the identification of the pathogenetic mechanism for the syndrome.